Complete correction of transposition of the great arteries with left juxtaposition of the atrial appendages. Issue 2 (April 1976) - Vidne, B A; Subramanian, S
Abstract : Juxtaposition of the atrial appendages is an uncommon anomaly which is usually associated with transposition of the great arteries. Experience with five patients with transposition of the great arteries in combination with juxtaposition of the atrial appendages in whom Mustard's operation was performed is reviewed. Technically, the existence of juxtaposition of the atrial appendages in corrective surgery for transposition does not present any additional surgical problems. Emphasis is placed on the advantages of early complete correction, avoiding the need for palliative procedure.